Correlations for the combustible sulfur contents of Turkish coals from sulfur forms and CaO analyses - (:unkn) unknown (ELSEVIER SCI LTD, 1997)
Total and combustible sulfur, CaO, ash and sulfur forms in 19 selected Turkish coals with widely varying characteristics (from bituminous coal to low-grade lignite) were determined according to ASTM standards. The total sulfur, combustible sulfur and CaO contents (wt% db) varied over wide ranges: 0.5-12.9, 0.25-12.8 and 0.4-14.1 respectively. Correlations based on the pyritic, organic and sulfate sulfur forms gave better results than those based on total sulfur. Inclusion of the CaO content in the correlations also affected the results favourably. (C) 1997 Elsevier Science Ltd.
Keywords: coal; combustible sulfur content; correlations; FLUIDIZED-BED COMBUSTOR; OXIDATION; RETENTION; ASH; PYRITE; FUEL